Total Artificial Heart, Augmented by Venovenous Extracorporeal Membrane Oxygenation. Issue 4 (July 2016) - Lick, Scott D.; Tran, Phat L.; Kazui, Toshinobu; Smith, Richard G.; Khalpey, Zain I.
Abstract : Shortly after SynCardia total artificial heart (TAH) implant, venovenous extracorporeal membrane oxygenation (ECMO) via a 31 Fr Avalon cannula was used for profound hypoxic lung dysfunction. Immediately after starting ECMO, TAH flow increased by 1.5–2.0 L/min, presumably because of augmented TAH filling by the ECMO jet.